2006
DOI: 10.1093/ndt/gfl006
|View full text |Cite
|
Sign up to set email alerts
|

Application of NKF-K/DOQI Clinical Practice Guidelines for Bone Metabolism and Disease: changes of clinical practices and their effects on outcomes and quality standards in three haemodialysis units

Abstract: The only way to ensure that K/DOQI guidelines actually improve medical outcomes is to emphasize implementation strategies and also the scientific evaluation of their effectiveness in clinical settings. In spite of the application of the K-DOQI recommendations, a large proportion of our patients stayed outside the proposed targets, which points to the need for more effective therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 16 publications
3
40
0
3
Order By: Relevance
“…Most concerning was that only 5 to 7.3% of dialysis patients simultaneously met all four targets (PTH, Ca, P, and Ca ϫ P). According to one study that evaluated target achievement both before and after the KDOQI treatment guidelines were introduced, a majority of patients remained outside at least some of the target ranges even after implementation (6.6 and 10.9% met all for targets in 2003 and 2004, respectively) (12). Another study evaluated the effects of guideline-induced changes in non-calcium-containing phosphate binders, vitamin D use, and dialysate calcium levels and found that serum P and serum PTH levels increased in association with a modest reduction in serum Ca (14).…”
mentioning
confidence: 99%
“…Most concerning was that only 5 to 7.3% of dialysis patients simultaneously met all four targets (PTH, Ca, P, and Ca ϫ P). According to one study that evaluated target achievement both before and after the KDOQI treatment guidelines were introduced, a majority of patients remained outside at least some of the target ranges even after implementation (6.6 and 10.9% met all for targets in 2003 and 2004, respectively) (12). Another study evaluated the effects of guideline-induced changes in non-calcium-containing phosphate binders, vitamin D use, and dialysate calcium levels and found that serum P and serum PTH levels increased in association with a modest reduction in serum Ca (14).…”
mentioning
confidence: 99%
“…18 However, it is difficult to fulfill all guideline targets simultaneously. 19 This may be particularly true for patients with SHPT who are resistant to calcitriol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…29 The consistent achievement of KDOQI goals for bone and mineral metabolism has been difficult with standard therapy, with a large proportion of patients exhibiting persistent and refractory SHPT. [30][31][32][33] Not surprisingly, only about 6.6% and 10.9% of dialysis patients simultaneously met KDOQI targets for PTH, phosphorus, calcium, and calcium-phosphorus product levels in 2003 and 2004, respectively. 32 Presumably, this is related to the fact that attempts to suppress serum PTH with increasing doses of active vitamin D analogues are limited by the development of hypercalcemia and worsening hyperphosphatemia.…”
Section: Safety Profilementioning
confidence: 99%
“…[30][31][32][33] Not surprisingly, only about 6.6% and 10.9% of dialysis patients simultaneously met KDOQI targets for PTH, phosphorus, calcium, and calcium-phosphorus product levels in 2003 and 2004, respectively. 32 Presumably, this is related to the fact that attempts to suppress serum PTH with increasing doses of active vitamin D analogues are limited by the development of hypercalcemia and worsening hyperphosphatemia. 33 The likelihood of developing hypercalcemia with active Vitamin D analogues is further increased by the concomitant use of calcium-containing phosphate binders.…”
Section: Safety Profilementioning
confidence: 99%